Políticas de aprendizagem ao longo da vida em Portugal: Controvérsias na esfera pública em torno da Iniciativa Novas Oportunidades (2005-2013) - Ana Paula Natal; Mariana Gaio Alves (Universidade do Minho, 2016)
This article seeks to contribute to a deeper understanding of the policiespursued in Portugal, since 2005, around the idea of lifelong learning, whichwas considered by the various Member States of the European Union as thebest way to meet the Lisbon Strategy. Within this framework, a considerableprominence of the measures and results associated with theIniciativa NovasOportunidades[New Opportunities Initiative] - a program designed to raise thePortuguese population's level of qualifications to the secondary-school level -was identified in the media. Taking as object of study the texts published inthree national newspapers - Expresso, Públicoand Correio da Manhã- in theperiod between 2005 and 2013, and using discourse analysis, we analysedhow the policy on adult education within the Iniciativa Novas Oportunidadeswas interpreted in the Portuguese newspapers. We have found a diversity ofperspectives and interests at stake, showing the strong impact that the adulteducation had in the media, the critical points of this policy and challenges tobe faced within lifelong learning.